Analysis of Digital Transformation in MSMEs to Support Local Economic Growth - Heppi Syofya; Prama Widayat; Deki Irawan; Suherman Suherman; Deby Anggun Sari (Politeknik Siber Cerdika Internasional, 2026)
Background: MSMEs are crucial for employment and economic growth, but must adopt and effectively use digital technology to stay competitive. Objective: This study aims to analyze the effectiveness of digital technology adoption among MSMEs in accelerating local economic growth. Methods: Following the PRISMA 2020 guidelines, a systematic literature search was conducted using Google Scholar, the Directory of Open Access Journals (DOAJ), and SINTA-indexed journals. Boolean search strings, such as “digital transformation” AND “MSME” AND “local economic growth,” were applied. Open-access articles published in Indonesian or English between 2021 and 2026 were included. From an initial pool of 47 records, 18 articles met the inclusion criteria and were examined through qualitative thematic synthesis. Results: The thematic synthesis of the 18 articles identified three dominant mechanisms through which digital transformation strengthens MSME performance: (1) market expansion through e-commerce and digital marketing, (2) improved operational efficiency through cloud-based management systems, and (3) increased economic participation facilitated by financial technology (fintech) adoption. The quantitative studies reported productivity gains of up to 30% and sales increases of up to 60% among digitally transformed MSMEs. However, the effects varied across regions and business sizes and were influenced by the availability of digital infrastructure and the organizational readiness of MSMEs. Conclusion: Digital technology helps MSMEs expand market reach and improve efficiency, profitability, and resilience, contributing to local economic growth through increased activity and employment. However, its adoption is still hindered by limited digital skills, unequal infrastructure, restricted capital access, and weak organizational strategies.